Classification of topologically conjugate affine mappings - Budnyts'ka, T. V. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
We consider affine mappings from ℝ^n into ℝ^n, n ≥ 1. We prove a theorem on the topological conjugacy of an affine mapping that has at least one fixed point to the corresponding linear mapping. We give a classification, up to topological conjugacy, for affine mappings from ℝ into ℝ and also for affine mappings from ℝ^n into ℝ^n, n > 1, having at least one fixed point and the nonperiodic linear part.